A multi-dimensional model for assessing e-government service gaps in the context of a developing country : a critical realist perspective - Mahlangu, Gilbert (Cape Peninsula University of Technology, 2021)
Literature reports that e-government services have been in use in developing countries for approximately two decades. Hence, consumers of government services would have expected some e-government maturity in the continuum, where e-services would have evolved to some degree. However, despite the deliberate efforts towards the design, development and deployment of e-government projects in developing countries, e-government service gaps still exist. Also, since the emergence of e-government in developing countries, several different measurement metrics in the form of models and frameworks have been utilised to evaluate e-government projects. Nevertheless, while e-government assessment typologies have developed over time, no measurement metrics exist to assess e-government service gaps according to the best knowledge of the researcher. Consequently, a failure to assess e-government service gaps makes it difficult to take well-founded improvement actions since these gaps are not obvious to the designers and implementers of e-government systems. Hence, the purpose of this study was in twofold: to investigate the factors enhancing e-government service gaps in the context of a developing country from multiple perspectives and develop a model for assessing e-government service gaps in the same context. To accomplish this purpose, the study performed an integrated literature review as well as construct analysis. Also, a conceptual model for assessing e-government service gaps was developed in Chapter Three. The study was grounded on the tenets and assumptions of the philosophy of critical realism. A sequential multi-methodology design was used to collect quantitative and qualitative data. Since the researcher aimed to understand the phenomenon from multiple perspectives, data was collected from three units: government employees; business; and citizens. A total of five hundred and fifty (550) questionnaire surveys were used to examine the factors enhancing e-government service gaps and evaluate dimensions for measuring service gaps while thirty (30) in-depth semi-structured interviews were used to gain a comprehensive understanding of factors enhancing e-government service gaps in a developing context, a purpose that could not be achieved through the use of structured questionnaire survey alone. The findings from questionnaires and interviews together with feedback from expert reviews were used to validate the conceptual model presented in Chapter Three. The deployment of e-government projects that provide comprehensive e-government services lies in the identification of e-government service gaps and addressing factors that enhance them. The study has revealed several factors that can explain why e-government service gaps exist in the context of a developing county. These include lack of requisite infrastructure; lack of interoperability; lack of access; lack of e-government funding; budget disparity; policy inconsistency; lack of the desire to support and coordinate e-government; design-reality gap; lack of user-involvement; and lack of developed IT human capacity. The factors identified in this study act as underlying mechanisms of successful implementation and utilisation of e-government in the developing context. For instance, electrical power outages and lack of ICT infrastructure make e-government a difficult goal to achieve. Besides, most of the factors appear to be greatly related to the socio-economic conditions prevailing in many developing countries. Therefore, until these factors are converted into enablers for providing comprehensive services, e-government service gaps will continue to exist in developing countries. Accordingly, the deployment of e-government services in developing countries with a focus on these underlying factors will to some extent reduce e-government service gaps and increase the utilisation of e-government services and user satisfaction. Also, the study envisaged that a multi-dimensional model for assessing e-government service gaps should comprise of four (4) constructs as follows: system functionality; service delivery; service gaps; and user satisfaction. This study provided novel contributions in a stratified fashion which was informed by the Three Worlds Framework as follows: (a) pragmatic world; (b) knowledge domain; and (c) philosophy of science. Some of the contributions include: enlightening the implementers and funders of e-government projects on factors that obstruct the successful implementation and utilisation of e-government services in the developing context; the model will allow for the identification of service gaps in a particular project that could be otherwise unnoticed during the design phase of e-government projects; thereby, contributing to the continuous improvement of e-government services; the findings provide theoretical knowledge to the body of literature concerning the factors that contribute to e-government service gaps; building on corpus literature on e-government assessment typologies, this study proffers a theoretical model for assessing e-government in the context of a developing country; the use of multi-methodology enabled consistency of reality in the study of e-government service gaps in the developing context; this study informs critical realists on the use of statistical inferences to explain the causal mechanisms of a given phenomenon based on regression analysis and in-depth interviews. In terms of further research, the study suggests that new insights on factors enhancing e-government service gaps could emerge if the research is undertaken again in more case studies; the study also suggests that future research in investigating e-government service gaps should include the marginalised communities.